The Nature of Magnetoelectric Coupling in Pb(Zr, Ti)O3–Pb(Fe, Ta)O3. (9th September 2015) - Evans, Donald M.; Alexe, Marin; Schilling, Alina; Kumar, Ashok; Sanchez, Dilsom; Ortega, Nora; Katiyar, Ram S.; Scott, James F.; Gregg, J. Marty
<x xml:space="preserve">Abstract</x> The coupling between magnetization and polarization in a room temperature multiferroic (Pb(Zr, Ti)O3–Pb(Fe, Ta)O3) is explored by monitoring the changes in capacitance that occur when a magnetic field is applied in each of three orthogonal directions. Magnetocapacitance effects, consistent with P2M2 coupling, are strongest when fields are applied in the plane of the single crystal sheet investigated.